Molecularly imprinted polymers in hybrid materials using inorganic nanoparticles - Ruiz-Córdova, Gerson; López, Rosario; Vega-Chacón, Jaime; Khan, Sabir [UNESP]; Picasso, Gino; del Pilar Taboada Sotomayor, Maria [UNESP] (My University, 2020)
Molecularly imprinted polymers (MIPs) have been widely implemented in the elaboration of analytical tools for the detection and separation of molecules due to their capacity of interacting specifically with target molecules. Molecular imprinting expertise is a possible synthetic route for preparing materials with mimic recognition function towards target molecules on the nanosized surface with high binding capacity and mass transfer rate. However, the MIPs could present some drawbacks, particularly, in extended washings to remove the template, related to the tedious procedures of grinding, irregular particle in size and shape and low reproducibility that would cause limit their practical applications. Inorganic nanoparticles-MIPs hybrid materials in a core-shell structure (IN-MIPs) present some features that allow overcoming the limitations of conventional MIPs. The core is composed of inorganic nanoparticles such as silica nanoparticles (SiO2), superparamagnetic iron oxide nanoparticles (SPION) and semiconductor nanoparticles, mainly quantum dots (QD). After an appropriate modification of the surface of the nanoparticles, the MIP matrix is formed around the nanoparticles and a hybrid material in a core-shell structure is obtained. This chapter reviews the recent advances in the preparation and applications of IN-MIPs. Due to the specific binding sites, the resulting IN-MIP exhibits good selectivity, reproducibility, high binding capacity and fast kinetics for the rebinding of the analyte. Additionally, this chapter summarizes the challenges and opportunities related to the suitable applications of the systems in chemical analysis (sensors), extraction of target molecules (solid-phase extraction), among others.
Keywords: Core-shell materials; Hybrid MIPs; Magnetite; Quantum dots; Silica